Allogenous Tendon Stem/Progenitor Cells in Silk Scaffold for Functional Shoulder Repair - Weiliang Shen; Jialin Chen; Zi Yin; Xiao Chen; Huanhuan Liu; Boon Chin Heng; Weishan Chen; Hong-Wei Ouyang (Cell Transplantation, 2012)
Tendon stem/progenitor cells (TSPCs) were recently identified within tendon tissues. The aim of this study was to investigate TSPC-seeded knitted silk—collagen sponge scaffold for functional shoulder repair. The multidifferentiation potential, proliferation, and immune properties of TSPCs were investigated in vitro, while the efficacy of TSPC-seeded knitted silk—collagen sponge scaffolds in promoting rotator cuff regeneration was evaluated in vivo within a rabbit model. TSPCs, which exhibited universal stem cell characteristics (i.e., clonogenicity, high proliferative capacity, and multidifferentiation potential), nonimmunogenicity, and immunosuppression, proliferated well on our scaffold in vitro. Implantation of allogenous TSPC-seeded scaffolds within a rabbit rotator cuff injury model did not elicit an immunological reaction, but instead increased fibroblastic cell ingrowth and reduced infiltration of lymphocytes within the implantation sites at 4 and 8 weeks postsurgery. After 12 weeks, the allogenous TSPC-treated group exhibited increased collagen deposition and had better structural and biomechanical properties compared to the control group. This study thus demonstrated that the allogenous TSPC-seeded knitted silk—collagen sponge scaffold enhanced the efficacy of rotator cuff tendon regeneration by differentiating into tenocytes, and by secreting anti-inflammatory cytokines that prevent immunological rejection. Hence, allogenous TSPC-seeded knitted silk—collagen sponge scaffolds can be a clinically useful application for tendon tissue engineering.